Analisis Pengaruh Harga, Lokasi Usaha, Kualitas Pelayanan, Fasilitas, Lama Usaha, dan Literasi Pendidikan Masyarakat terhadap Laba Bersih Usaha Fotokopi di Wilayah Pulau Lombok - Ridian Hadad Abiwan; Jumaidi, Lalu Takdir (Fakultas Ekonomi dan Bisnis Unram, 2024)
This study is intended to test the effect of price, business location, service quality, facilities, length of business, and community education literacy on the net profit of photocopying businesses on the island of Lombok. The type of research used is associative quantitative research. The sample was obtained by purposive sampling method and 35 photocopying businesses were selected. The data analysis tool used was Statistical Product and Service Solutions (SPSS) version 25. The results of this study indicate that the variables of price, business location, service quality, facilities, length of business, and community education literacy have a significant positive effect on the net profit of photocopying businesses in the Lombok island region.